Soft skills: a Quranic perspective - Mohamad, Nor Asiah (2010)
Soft skills are essentials in human development. Al Quran itself is a source of knowledge for all, Muslims and non Muslims. Al Qur an speaks on various basic human skills. It also looks at all the elements of soft skills as identified by the MOHE as basic human skills employing various approaches and methods. Some of the skills are further clarified through the teaching of the Prophet Muhammad saw. This paper highlights the basic human skills and its importance. It is to prove that a practicing Muslim should possess all the good values as part of the religious requirement as well as professionalism requisite. As such , in particular, a graduate of any Muslim institutions in which the syllabuses have incorporated Islamic teaching should practice and portray the values in his life, seen by others, impactful to the community and system and thus become a high demand worker in any organization.